Crystal structure of 1,2-bis(2,4-dinitro-1H-imidazol-1-yl)ethane – dimethylformamide (1/1), C11H13N9O9 - Jun Yuan; Bingheng Wu; Yong Wang; Jianlong Wang; Duanlin Cao; Lizhen Chen (Zeitschrift für Kristallographie - New Crystal Structures)
C11H13N9O9, triclinic, P1‾$P\overline{1}$ (no. 2), a = 8.6588(3) Å, b = 8.7538(3) Å, c = 11.7312(4) Å, α = 78.230(1)°, β = 82.060(1)°, γ = 76.031(1)° V = 841.05(5) Å3, Z = 2, Rgt(F) = 0.0376, wRref(F2) = 0.1006, T = 150.0 K.